Acid mine drainage, rock drainage, and acid sulfate soils : causes, assessment, prediction, prevention, and remediation - Jacobs, James A. (James Alan), 1956-; Lehr, Jay H., 1936-; Testa, Stephen M. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
Written to help readers understand the formation of AMD, Acid Mine Drainage addresses the generation of acidic waters usually from both used and abandoned coal or metal mines. Offering the most up-to-date ideas on metals remediation, which makes finding control methods relatively easy, the text provides a section on legal and policy issues and details the causes, control, prediction, prevention, and remediation of AMD formation. Case studies from North America, Europe, Asia, and developing countries highlight various approaches to AMD problems.
6 Natural Acid Rock Generation, Drainage, and Metal Leaching: Impact on Exploration, Mining, and ReclamationIntroduction; Acid Rock Drainage; Gossan Formation; Supergene Mineralization; Acid Rock Generation and Drainage Through Time; Natural Metal Concentrations; Geoenvironmental Models; Conclusions; Acknowledgment; References and Suggested Reading; 7 The Sulfur Cycle: Acid Drainage and Beyond; Some Background And Fundamentals Of Microbial Life; Review of the Chemistry of Acid MineDrainage; The Origin and Evolution of Life onEarth; Important Background Details; The Origin of Life.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Acid mine drainage; Mine drainage; Rock drainage; TECHNOLOGY & ENGINEERING -- Mining; Acid mine drainage; Electronic books